A test of technology acceptance model in the use of social media among PR practitioners in Nigeria - Syed Abdullah Idid, Syed Arabi; El-Kasim, Mukhtar (Taylor's University, 2016)
Many public relations scholars believed that, the emergence of social media has accentuated the public relations practice in recent times. Social media provides public relations practitioners opportunities for creating, sharing, posting, documenting as well as interacting communication content on the net between organizations and their key public members for enhancing mutual and long-term positive relationships. The purpose of this paper was to investigate whether the perceived usefulness and ease of use of social media influence the behavioral intention of practitioners to use it for the enhancement of mutual relationships between with their publics. The Technology Acceptance Model (TAM) was adopted as the theoretical guide of this study. Using self-administered questionnaire, data were collected from 513 practitioners and analyzed through Statistical Package for Social Sciences (SPSS). The results revealed that perceived usefulness (β=.251, t=4.723, p=.00) and perceived ease of use (β=.514, t=9.649, p=.000) exerted significant positive effect on the PR practitioners’ behavioral intention to accept social media for enhancing mutual relationships. Further, the results suggested that perceived ease of use had a significant indirect effect on behavioral intention through perceived usefulness. In addition, it was found that, practitioners’ perception on the ease of use of the social media was the strongest indicator for its utilization for the enhancement mutual relationships. Recommendations and limitations are further discussed.